2020
DOI: 10.1103/physrevb.101.014440
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy and low-field magnetic phase diagram of the quasi-two-dimensional ferromagnet Cr2Ge2Te6

Abstract: In this work we present a comprehensive investigation on magnetic and thermodynamic properties of the two-dimensional layered honeycomb system Cr2Ge2Te6. Using magnetization and specific heat measurements under magnetic field applied along two crystallographic directions we obtain the magnetic phase diagram for both directions. Cr2Ge2Te6 is a ferromagnet with a Curie temperature TC = 65 K and exhibits an easy magnetization axis perpendicular to the structural layers in the ab-plane. Under magnetic fields appli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 51 publications
5
16
0
Order By: Relevance
“…[9]. As-grown single crystals were thoroughly characterized by powder x-ray diffraction and energy dispersive x-ray spectroscopy; both agree well with the crystal structure in the R3 space group as well as with the expected stoichiometry of Cr 2 Ge 2 Te 6 [12].…”
Section: Samples and Methodssupporting
confidence: 60%
“…[9]. As-grown single crystals were thoroughly characterized by powder x-ray diffraction and energy dispersive x-ray spectroscopy; both agree well with the crystal structure in the R3 space group as well as with the expected stoichiometry of Cr 2 Ge 2 Te 6 [12].…”
Section: Samples and Methodssupporting
confidence: 60%
“…Interestingly, we observed that the maximal T * C increase by mechanical strain was as much as 2.5 ± 0.6 K at ∆ ≈ 0.016%. This is comparable to what was previously achieved in bulk CGT by applying an out-of-plane magnetic field of 0.7 − 1 T [2,8], proving that strainbased nanomechanical methods provide a compelling route for controlling and probing magneto-elastic coupling in ferromagnetic 2D layers and heterostructures.…”
supporting
confidence: 80%
“…In contrast to many other 2D layered ferromagnetic compounds [4], CGT exhibits inter-and intra-layer ferromagnetic coupling for any number of layers [2]. Recent progress has been made in manipulating the magnetic order of CGT using electrostatic gating [6,7], magnetic field [2,8], pressure [9,10], ion intercalation [11] and via spin-orbit torque [12,13]. However, an experimental coupling of magnetic order to mechanical strain in thin CGT was left unattended, since strain in thin layers is conventionally a difficult parameter to control.…”
mentioning
confidence: 99%
“…The saturation magnetization of Cr 2 Ge 2 Te 6 (3.24 μ B /Cr) thin film is consistent with the reported value (≈ 3.1 μ B /Cr) for bulk single crystal and thin films. [23,43,44] However, Cr 2 Si 2 Te 6 (1.02 μ B /Cr) had a saturation magnetization slightly lower than that of the bulk single crystal (≈ 2.86 μ B /Cr). [45,46] The exact reason for this lower saturation magnetization of Cr 2 Si 2 Te 6 thin film needs further investigation, since, there is no reference data for magnetization of Cr 2 Si 2 Te 6 thin film.…”
Section: Crystal Structure and Magnetic Characterization Of The Thin Filmmentioning
confidence: 98%